ANALISA KEBUTUHAN RUANG PADA KAWASAN PERBELANJAAN CITRA NIAGA SAMARINDA - Ramadhan, Muhammad Akmal Alfaridzi; Suryadjaja, Regina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
The Citra Niaga sector of Samarinda City is a commerce area that has grown to be one of the popular tourist spots for East Kalimantan suvenir buying. The Citra Niaga area, which competes with Soekarno Hatta Airport, was granted the Aga Khan Award for Architecture (AKAA) in 1989. It is a market area designed to serve small to large traders that offer suvenirs and other trade items. However, the Citra Niaga neighborhood started to become deserted in the late 1990s due to the construction of more contemporary commercial malls, which caused traders and tourists who had previously frequented the area to gradually move elsewhere. Because of this, Citra Niaga Samarinda had experienced its dark period, where visitors who came there were drastically reduced and the government's attention at that time, so that many problems then arose in the area, for example, the decline in building functions, inadequate supporting facilities, the emergence of illegal parking pockets, and so on. For this reason, this research aims to provide recommendations for the concept of utilization of space requirements which can then be proposed for the preparation of the concept of structuring the area to revive the Samarida Commercial Image area so that it can become a shopping tourist destination area for suvenirs typical of East Kalimantan. This research uses standard space requirements guidelines issued by the government and recognized institutions. The analysis used by the author is a descriptive analysis of the existing conditions in the Citra Niaga area. Keywords:  commercial area; shopping tourism; souvenirs Abstrak Kota Samarinda memiliki sebuah kawasan perdagangan yang menjadi salah satu kawasan destinasi wisata perbelanjaan cenderamata khas Kalimantan Timur, kawasan tersebut adalah kawasan Citra Niaga. Citra Niaga merupakan kawasan perdagangan yang dimana diperuntukkan sebagai tempat usaha pedagang kecil hingga besar yang berjualan cenderamata dan barang dagang  lainnya, kawasan Citra Niaga pernah memperoleh penghargaan Aga Khan Award for Architecture (AKAA) pada tahun 1989 yang bersaing dengan Bandara Soekarno Hatta. Namun sejak akhir dekade 90an kawasan Citra Niaga mulai ditinggalkan, dimana hadirnya pusat perbelanjaan yang lebih modern sehingga para pedagang dan pengunjung yang pada awalnya mengunjungi kawasan Citra Niaga mulai perlahan meninggalkan kawasan Citra Niaga. Dikarenakan hal itu Citra Niaga Samarinda sempat mengalami masa kelamnya, dimana para pengunjung yang datang kesana berkurang drastis dan perhatian pemerintah pada saat itu, sehingga banyak permasalahan yang kemudian muncul di kawasan tersebut contohnya saja adalah penurunan fungsi bangunan, fasilitas pendukung yang kurang memadai, munculnya kantong parkir liar, dan lain sebagainya. Atas hal tersebut penelitian ini bertujuan untuk memberikan rekomendasi konsep pemanfaatan kebutuhan ruang yang kemudian dapat usulan penyusunan konsep penataan kawasan untuk  menghidupkan kembali kawasan Citra Niaga Samarinda sehingga dapat menjadi kawasan destinasi wisata perbelanjaan cenderamata khas Kalimantan Timur. Penelitian ini menggunakan standar pedoman kebutuhan ruang yang dikeluarkan oleh pemerintah dan lembaga yang diakui. Adapun analisis yang digunakan oleh penulis adalah analisis deskriptif kualitatif mengenai kondisi eksisting pada Kawasan Citra Niaga.